2018
DOI: 10.3892/or.2018.6511
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Girdin suppresses the malignant behavior of colorectal carcinoma cells

Abstract: The aim of the present study was to investigate the effect of the actin‑binding protein Girdin on the proliferation, invasion and migration of colorectal cancer (CRC) cells. Cultured CRC cells (LoVo cell line) were transfected by Girdin‑specific and control shRNA constructs and analyzed for proliferation, invasion and migration by the MTT, Transwell and wound‑healing assays, respectively. The activation of the Janus kinase/signal transducer and activator of transcription (JAK/STAT) signaling pathway and expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It is important to note that the pattern of pS245GIV staining is strikingly different from the levels of total GIV during CRC initiation and progression; we have previously shown that GIV mRNA and protein generally decreases first during polyp formation and progression and subsequently increases during CRC progression to metastasis . We and others have shown that increased levels of GIV in established CRCs correlate with aggressive features (Garcia-Marcos et al, 2011b;Jun et al, 2013;Aznar et al, 2016;Barbazan et al, 2016;Ghosh et al, 2016;Lu et al, 2018), for example, shorter metastasis-free survival, chemoresistance, and stemness, largely attributed to its ability to scaffold multi-receptor signaling cascades and enhance them via G protein intermediates to trigger epithelial mesenchymal transition (reviewed in Ghosh (2015)). Taken together, the loss of pS245 GIV early during polyp to CRC progression underscores how GIV may serve as a tumor suppressor when localized to TJs in the polarized normal epithelium before it assumes its role as an enhancer of epithelial-mesenchymal transition and stemness in established CRCs.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that the pattern of pS245GIV staining is strikingly different from the levels of total GIV during CRC initiation and progression; we have previously shown that GIV mRNA and protein generally decreases first during polyp formation and progression and subsequently increases during CRC progression to metastasis . We and others have shown that increased levels of GIV in established CRCs correlate with aggressive features (Garcia-Marcos et al, 2011b;Jun et al, 2013;Aznar et al, 2016;Barbazan et al, 2016;Ghosh et al, 2016;Lu et al, 2018), for example, shorter metastasis-free survival, chemoresistance, and stemness, largely attributed to its ability to scaffold multi-receptor signaling cascades and enhance them via G protein intermediates to trigger epithelial mesenchymal transition (reviewed in Ghosh (2015)). Taken together, the loss of pS245 GIV early during polyp to CRC progression underscores how GIV may serve as a tumor suppressor when localized to TJs in the polarized normal epithelium before it assumes its role as an enhancer of epithelial-mesenchymal transition and stemness in established CRCs.…”
Section: Resultsmentioning
confidence: 99%
“…Girdin is highly expressed in various human malignancies, including breast, colon, lung, thyroid and cervical cancer (37)(38)(39)(40). The Department of Gastroenterological Surgery, Nagoya City University Graduate School of Medical Sciences also reported that high Girdin expression was present in esophageal cancer and it is correlated with invasive potential and prognosis (14).…”
Section: Discussionmentioning
confidence: 99%
“…Girdin is highly expressed in serval cancers (Lu, et al, 2018, Shibata et al, 2013, Wang et al, 2017), and downregulation of Girdin suppressed colorectal cancer cell migration and invasion (Lu et al, 2018). Consistence with the reported studies, herein, we found that Girdin was upregulated in human EOC (Figure 1), and knockdown of Girdin inhibited migration and invasion of EOC cells (SKOV3 and A2780), and retarded the expressions of MMP2/9 (invasive and metastatic factors), however, overexpression of Girdin resulted in the opposite (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that Girdin is a regulator of cell motility and implicated in cancer cell migration, particularly through enhancing the activity of AKT (or phosphoinositide 3‐kinase [PI3K]‐Akt signal transduction pathway), which plays a core role in EOC cell migration and polarization (Mullerova et al, Wang et al, 2017, Weng et al, 2010). Girdin is highly expressed and emerged as therapeutic target in colorectal cancer, breast cancer as well as esophageal squamous cell carcinoma (Lu et al, 2018, Shibata et al, 2013, Wang, et al, 2017). However, whether and how does Girdin function in human EOC remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%